Pengaruh Perkembangan Demokrasi dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi di Indonesia - Novanto, Ferdy Senja Putra; Prabowo, Prayudi Setiawan (Jurnal Ekonomika : INDEPENDEN, 2024)
Institutional economics explains that the economy works influenced by rules/norms. This study aims to determine the effect of democratic development and human development index on economic growth in Indonesia. This study takes 34 provinces in Indonesia in the 2015-2020 period as a sample. Independent variables include civil liberties, political rights, democratic institutions, and human development index. Meanwhile, economic growth is the dependent variable. Panel data regression analysis using Eviews is the analytical technique applied in this study. The use of the Fixed Effect Model (FEM) shows the research findings that, 1) simultaneously the independent variables have a significant effect on the dependent. 2) Partially, the civil liberties variable is negatively and significantly related, 3) the political rights variable has no effect, 4) the democratic institutions variable has a positive and significant effect 5) and the human development index negatively and significantly affects economic growth.